Rare Diseases Recent Advances - Kanayochukwu Nduka, John; Akarsu, Sevgi (IntechOpen, 2023)
Life expectancy is often associated with economic, educational, and public health development. These factors were previously thought to be the exclusive privilege of the developed countries of the world, but the outbreak of COVID-19 seemingly evened the global playing field. COVID-19, the Ebola virus, and HIV and AIDS were considered "rare diseases" at the time of their occurrence and their outbreaks led to new thinking about public health issues. Technological advancements in telecommunication, aviation, industrial processing, agriculture, military armaments, and more, along with their impacts on climate and environment, have led to increasing levels of contaminants, posing a major public health problem. Exposure to toxins and chemicals via processed foods, work/occupation, or the environment is increasingly causing rare diseases that are difficult to diagnose and treat, especially in undeveloped areas of the world with inadequate health facilities and diagnostic skills. This book examines some of these rare diseases. It includes nine chapters that discuss conditions such as Behcet's disease, malignant mesothelioma, dentofacial anomalies, neuropathic pruritus, lipoatrophia semicircularis, and short QT syndrome.